THE APPROACH TO ASSESSING THE FORMATION OF SPECIAL COMPETENCES - A. N. Pechnikov; A. V. Prenzov (Образование и наука)
The aim of the publication is the justification of the approach to assessing the degree of formation of special competencies.Methodology and research methods. The methods of analysis and synthesis are used in the work.Results and scientific novelty. Various interpretations of special competence due to their compliance with the actual contents of the Federal State Educational Standards (FSES) are considered. The requirements to the characteristic are determined, adequately reflecting the formation of the special competence. The compossibility of the level of assimilation to these requirements is justified. The features of the level of assimilation as a measurement object are considered. The correspondence between levels of assimilation and those kinds of tasks that can be used for their assessment (identification) is established. The model of measurement of special competences is proved. The types of tasks corresponding to the diagnosed levels of assimilation of professional abilities, skills and abilities are  emphasized.Practical significance. The approach to the choice and development of tools for identification of formation of special competences is offered.